Laying More Pipe - Weishaus, Joel (UnderCurrents: Journal of Critical Environmental Studies, 2014)
With pick and shovel, find the broken cast iron pipe, pry out old lead, knock off rusty joints. 20’ of 4” 40-schedule ABS sawed and coupled with rubber collars with stainless steel braces, joined to pipe at next stream crossing, joined to terra cotta pipe under tea house site, joined to three lengths iron pipe cut three poems ago. 1 lb brick of dull lead melted in a pan becomes silver liquid poured into iron bell-collars. Black cement smeared over all connections is a waterproof coating. Taps turned and draining, toilets flushed... Give it all back.